Illustration of Filariasis Surveilans in South Labuhanbatu Regency - Ade Rahimi; Toghur Arifani Lubis (Britain International for Academic Research (BIAR) Publisher, 2020)
Filariasis is a chronic infectious disease caused by filarial worms and transmitted by mosquito. Filariasis elimination program in Indonesia set with two pillars that are filariasis mass drug administration (POMP filariasis) in endemic areas and preventing or limiting disability due to filariasis. POMP minimum coverage by eighty five percent must be achieved to break the chain of transmission. This study is to describe filariasis mass drugs administration in south Labuhanbatu regency. Data were obtained from interview with the supervisor of filariasis program. The results show number of filariasis sufferer until two thousand sixteen is twenty nine patients. Every year founded new filariasis sufferer even some of them are died and there are puskesmas that has POMP coverage under eighty five percent or minimum standard.